Massage Therapy by Mother or Nurse: Effect on Weight Gain in Premature Infants - Zohreh Badiee; Shiva Samsamshariat; Pegah Pourmorshed (مجله دانشکده پزشکی اصفهان, 2011)
Background: Today, with the introduction of surfactant the survival rate of preterm infants was increased significantly and the researchers are looking to improve growth and development of premature infants. The effects of massage therapy on weight gain and bone mineralization in preterm infants has been shown in numerous studies. The purpose of this study was to compare the effect of massage therapy on weight gain in preterm infants. Methods: Our randomized clinical trial has three groups: the infants who only received usual care, those who received massage by an expert nurse and those who received massage by their mothers. Massage therapy was conducted three times a day for five consecutive days. We recorded daily weight gain, the length of hospital stay and fluid intake. We used one way ANOVA and Kruskal-Wallis tests by SPSS software. Findings: The gestational age ranged between 28 to 34 weeks. At the end of the fifth day the group who were massaged by a nurse had significantly more weight gain (6.5 ± 2.5%) compared to two other groups (P < 0.001). The weight gain in the group who were massaged by their mother was 4.6 ± 1% and in the usual care group was 3.7 + 1.5% (P < 0.05). There was no significant difference in the length of hospital stay among groups. Conclusion: This study showed that a five days massage therapy was a safe procedure for stable preterm infants to facilitate weight gain. Mothers can use this effective and low cost method for weight gain in their preterm infants.